2018
DOI: 10.1111/ajo.12802
|View full text |Cite
|
Sign up to set email alerts
|

Improved laparoscopic skills in gynaecology trainees following a simulation‐training program using take‐home box trainers

Abstract: A take-home box trainer simulation-training program was associated with improvement in laparoscopic skills. This type of program may improve trainee access to simulation training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…The beneficial impact that simulator-acquired skills have on real surgeries is today undeniable. The possibility of mentoring and learning in a non-stressful environment speeds up the learning curves and self-confidence of trainees, translating into better performance in clinical practice ( Wilson et al, 2019 ; Gala et al, 2013 ; Larsen et al 2009 ; Ahlborg et al, 2013 ; Lobão et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial impact that simulator-acquired skills have on real surgeries is today undeniable. The possibility of mentoring and learning in a non-stressful environment speeds up the learning curves and self-confidence of trainees, translating into better performance in clinical practice ( Wilson et al, 2019 ; Gala et al, 2013 ; Larsen et al 2009 ; Ahlborg et al, 2013 ; Lobão et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to Villani et al study, where all laparoscopic liver resections were pooled and the effect of time on outcomes was studied. 25 Second generation laparoscopic surgeons 26,27 benefit from fellowship training as well as mentoring schemes, 26 where the learning acquired by the pioneers is distilled down to the next generation of surgeons. In addition to surgical techniques, there has been a parallel improvement in laparoscopic equipment, such as advanced energy devices and visual display screen including 4K and 3D technology.…”
Section: Hpbmentioning
confidence: 99%
“…In addition to surgical techniques, there has been a parallel improvement in laparoscopic equipment, such as advanced energy devices and visual display screen including 4K and 3D technology. Courses in advanced laparoscopic training and the availability of simulators [27][28][29] to practise skills outside the operating theatre can all contribute towards a shorter learning curve for the next wave of laparoscopic HPB surgeons. In our study, risk adjustment using the Iwate index reduced the observed learning curves for both surgeons for the end point of operating time, but did not affect the CUSUM plot for conversion rate.…”
Section: Hpbmentioning
confidence: 99%
“…Support for at-home laparoscopic training has been growing in recent literature. Support first came with evidence of skill acquisition and construct validity for various developed tasks 6 , 7 , 8 , 9 , 10 , 11 . Randomized trials also demonstrated that skill acquisition with at-home trainers was equivalent to that of onsite trainers, proving this as a reasonable training alternative 12 .…”
Section: Introductionmentioning
confidence: 99%